Impact of Intellectual Capital on Firms’ Performance: With Perspective of Commercial Banks in Chitwan - Shrestha, Udaya Kumar (BMC Journal of Scientific Research, 2023)
Intellectual Capital (IC) is a term that refers to a firm’s strategic assets that assist to enhance the performance. The main purpose of this research is to examine the impact of Intellectual Capital on firms’ performance in with perspective of banking sectors. To assess the many aspects that can potentially have an impact on the performance of the firm, previous research and necessary documentation relating intellectual capital and its associated factors were reviewed. Similarly, descriptive and casual comparative research design were used. The population of this study is employees of commercial banks in Chitwan who hold the position of branch manager and/or above. To meet the objectives of this study, google form questionnaire was administered and sent to 75 branch managers. Out of which 48 responses were completed which were taken as sample that included tick mark questions, multiple-choice questions, and 5-point Likert scale questionnaires. The approach of non-probability purposive sampling was used. The dependent variable is firm performance, while the independent variable is Intellectual Capital (human, structural and customer capital). Data was analyzed using descriptive statistics (percentage, mean, and SD) and inferential statistics (correlation coefficient, multiple regression). The finding showed that customer capital was one of the most important determinants of a firm’s performance, but structural capital and human capital were not statistically significant predictors at the 5% level of significance. This study may be a valuable piece of research works for academicians, practitioners, and the management body of any concerned organizations.